East meets West: Spiritual tourism in Chinese protected areas - Shaohua Wang; Dani Blasco (Annals of Tourism Research Empirical Insights, 2022)
This article is a first attempt at studying the concept of spiritual tourism in Chinese protected areas, and examines this western concept within an eastern context. Data from the literature review and in-depth interviews were analysed through thematic analysis. Results show that although spiritual tourism is not widely acknowledged in China, spirituality related to nature has existed for millennia, especially through the concept of the unity of heaven and mankind (in Chinese, Tian Ren He Yi). Opportunities for developing and managing spiritual tourism in Chinese protected areas are suggested, and its challenges considered. This research adds an eastern viewpoint in order to acquire a broader understanding of spiritual tourism in different cultures and places.
Keywords: 330; China; Human-Nature relationship; Protected areas; Spiritual tourism